Study on Forced Marriage in the City of Zurich - (:unkn) unknown (My University, 2025)
Several counselling centres in the city of Zurich have remarked a recent increase in the numbers of individuals who seek advice for reasons of forced marriage. The actual extent of the problem is, how-ever, still unknown and there is hardly any information on the situation of those men and women who are affected by situations of forced marriage. Sensational reports in the media on cases of forced marriage among migrant communities have alarmed the Swiss public and threaten to create a back-lash against such communities. Much political controversy surrounds the topic. At present there are several efforts in Switzerland to create a law article prohibiting forced marriage. Academic research has remained rather silent on the issue of forced marriage. The aim of this research project is to provide a sound basis for understanding the phenomenon by: Addressing the issue of how forced marriage can be defined and where the boundaries between arranged marriage and forced marriage can be drawn Exploring the extent and reasons for forced marriage in the city of Zurich and examining the life situation of those individuals affected by it Identifying resources and adequate approaches for developing viable and sustainable responses, programmes and policies to protect individuals affected by forced marriage and to prevent future situations The study's approach centres on qualitative expert interviews with several specialists working in public government institutions as well as in private or half-private organisations in Switzerland. The aim of the interviews is to gain a wide spectrum of perspectives on the topic of forced marriage. The results of the study are addressed to specialists working in the fields of victim protection, violence prevention, migration, education and gender equality as well as to politicians, the media and further interested groups and individuals.
Keywords: forced marriage; domestic violence; ethnicization of sexism